Photodegradation of methylene blue dye and deactivation of E.coli and S.aureus using C.benghalensis zinc ferrite nanoparticles - Nomso C. Hintsho-Mbita; Matimane Maeko; Morongwa M. Mathipa; Zikhona N. Tetana (Desalination and Water Treatment)
Water is an essential element for various activities including industrial, agricultural and domestic. However, there is a limited accessibility of fresh water due to contaminants which are being released by the textile industries and bacterial strains which are causing a build-up of various contaminants. In this study, ZnFe2O4 NPs using Commelina benghalensis extract was synthesized and tested for the degradation of MB dye and the removal of bacteria in seeded and real water samples. UV–vis, XRD, FTIR, BET, PL and VSM were used to characterize the ZnFe2O4 NPs. XRD showed that our material has a cubic face structure and through FTIR the phytochemicals were deposited on the metal ferrites. For optical properties, the band gap of 3.7 eV was obtained. BET showed the ZnFe2O4 to be mesoporous, type II, and had the pore diameter of 28.47 nm. Upon testing its efficiency against MB dye, a 92 % degradation was recorded at optimal conditions of pH 11, 10 ppm and 50 mg dosage. The material could be reused up to 3 times with an 80 % efficiency. Furthermore, OH radicals were noted to be the species responsible for degradation. These materials were also potent during the deactivation of bacterial strains in both seeded and real water samples.